2017
DOI: 10.1002/adom.201700836
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Optical Band Gap in Epitaxial BiFeO3 Thin Films

Abstract: the pursuit of electric-field-controlled magnetism. [2] BFO is part of a larger family of ferroelectric oxides, important compounds that are relevant in the fields of optical modulation, [3] data storage, [4,5] actuation, [6] and sensing. [7] While many of these established applications are based on bulk samples (either single crystals or ceramics), there has recently been a substantial drive to exploit and enhance the desirable functional properties of ferroelectric oxides in thin film form. [8][9][10] Epitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 65 publications
5
48
0
Order By: Relevance
“…LaAlO 3 and YAlO 3 ) exhibits relatively larger optical band gap than on tensile substrate (e.g. DyScO 3 )[44,45,72,73].…”
mentioning
confidence: 99%
“…LaAlO 3 and YAlO 3 ) exhibits relatively larger optical band gap than on tensile substrate (e.g. DyScO 3 )[44,45,72,73].…”
mentioning
confidence: 99%
“…It is suggested that the higher growth rate for Sample B is the reason for such disordered domains. [ 4,41,42,50–53 ] Note that Sample C, grown by Nd:YAG laser with as‐grown mosaic domains [Figure 2e–h], can be converted by annealing to show a striped domain arrangement (discussed later).…”
Section: Resultsmentioning
confidence: 99%
“…While the domain arrangement for BFO films grown by excimer pulsed laser deposition (PLD) is typically stripe‐like, it has been found that BFO films fabricated by frequency‐tripled Nd:YAG laser (wavelength λ = 355 nm) consistently exhibit mosaic domains. [ 41–43 ] Here, we investigate the origins of such observations, i.e., despite identical mechanical and electrical boundary conditions, why such drastically different nanoscale domain topologies form. We show that the growth subtleties (likely related to the rapid growth rate [ 42 ] ) of the Nd:YAG laser PLD system induce an out‐of‐plane strain gradient over a 5 nm length scale directly above the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decade also saw exciting advancements in the understanding more nuanced features of thin‐film BFO, including its optical qualities, [ 64,82,83 ] the sensitivity of the spin texture to strain and applied magnetic field, [ 84 ] along with its strain‐ and composition‐driven phase behavior. [ 85 ] Concurrently, understanding the role of strain gradients and related flexoelectric response in epitaxial BFO gained prominence.…”
Section: Introduction To Bifeo3mentioning
confidence: 99%